E-cigarette Use and Risk Behaviors among Lesbian, Gay, Bisexual, and Transgender Adults: The Behavioral Risk Factor Surveillance System (BRFSS) Survey - Al Rifai, Mahmoud; Mirbolouk, Mohammadhassan; Jia, Xiaoming; Nasir, Khurram; Pickett, June; Nambi, Vijay; Ballantyne, Christie; Merchant, Anwar; Blaha, Michael; Virani, Salim (Kansas Journal of Medicine, 2020)
Introduction: We studied prevalence of e-cigarette use among lesbian, gay, bisexual, and transgender (LGBT) individuals and its association with risk behaviors.Methods: Using data from the Behavioral Risk Factor Surveillance System (BRFSS) survey, we assessed self-reported sexual orientation, e-cigarette use, cigarettes, marijuana, smokeless tobacco, and high-risk behavior (using non-prescribed drugs, treatment for sexually transmitted disease, or receiving monetary or drug compensation in exchange for sex in the previous year). We used multivariable-adjusted logistic regression models to study the association between LGBT and risk behaviors.Results: Prevalence of e-cigarette use among LGBT adults was 13%, nearly twice that of heterosexual adults. LGBT were more likely [Odds Ratio (95% Confidence Interval)] to report current use of e-cigarettes 1.84 (1.64,2.06), cigarettes 1.61 (1.49,1.73), marijuana 2.37 (1.99,2.82), and high-risk behavior 3.69 (3.40,4.01) compared to heterosexual adults. Results for smokeless tobacco were not significant.Conclusion: There are disparities in e-cigarette and other risk behaviors among LGBT adults, which may increase risk of adverse health effects in this vulnerable population.